PENGARUH AMBIGUITY, MARKET RISK PREMIUM, MARKET TO BOOK, SIZE, DAN MOMENTUM TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 PERIODE 2017-2018 - Rizqiyana, Amaliya; Arfianto, Erman Denny (Diponegoro Journal of Management, 2019)
The main purpose of investing in the capital market is to obtain a return. To achieve maximum return, it is necessary to know the factors that can influence stock returns. Therefore, this study aimed to determine the effect of ambiguity, market risk premium, market to book, size, and momentum on stock returns.The sample used in this study was company data that listed on the Indonesia Stock Exchange LQ45 index during the period 2017-2018. The method of determining sample was using a purposive sampling method and obtained 34 companies listed in LQ45. The method of hypothesis testing using different test t-test and multiple linear regression analysis.The results of this study indicate that size and momentum have a positive and significant effect on stock returns. Ambiguity has a positive and not significant effect on stock returns. Also market risk premium and market to book have a negative and not significant effect on stock returns.